The Insider Trading in the European Union Law (Global Journal of Management and Business Research, 2014)
Insider trading is the negotiation in stock market misusing privileged information by people who are in exclusive position to access to such information, should be informed the market as a "relevant fact", except in an ongoing operation, on which a legitimate interest to keep reserved is held. They are called corporate insiders. The determination of the legal system of the international financial operations with privileged information presents certain difficulties, due the absence of a common regulation, also in the European Union.
Keywords: insider trading; stock market; market of investment services; european union; privileged information